Survival outcomes and patterns of failure in women with stage IIIC2 endometrial carcinoma. (September 2017) - Lee, Joon K.; Mahan, Meredith; Hanna, Rabbie K.; Elshaikh, Mohamed A.
Abstract: Objectives: Para-aortic lymph node involvement in women with endometrial carcinoma (EC) is a poor prognostic factor. Many studies have included women with stage IIIC2 in cohorts of patients with advanced stage disease. The aim of this study was to analyze survival outcomes and patterns of failure in women with solely stage IIIC2 EC. Methods: We identified women with FIGO stage IIIC2 EC who underwent surgical staging at our institution. In addition to descriptive analyses of patient demographics, tumor characteristics, and adjuvant treatment received, univariate log-rank analyses and Cox regression multivariate analyses (MVA) were performed to identify predictors of recurrence-free (RFS), disease-specific (DSS) and overall survival (OS). Results: A total of 72 women were included in this study cohort. The median follow-up time was 43 months. The median number of positive para -aortic lymph nodes was one. Of the 61 women (84.7%) who received adjuvant therapy, 40 women (65.6%) received chemotherapy and radiation therapy (CRT), 17 women (27.9%) received chemotherapy alone (CT), and only 4 women (6.6%) received radiation therapy alone. Thirty-seven women (51.4%) experienced disease recurrence. Distant metastasis was the most common pattern of failure (73%). Five-year RFS, DSS, and OS were 48%, 51%, and 48%, respectively. Due to small study size, our exploratory multivariate analysis demonstrated that histologic grade was the only significant prognostic factor for DSS ( p = 0.03) and OS ( p = 0.02). The type of adjuvant therapy did not sustain its independent predictive significance for RFS, DSS and OS. Conclusions: Our findings suggest that almost half of women with stage IIIC2 can be cured with surgical staging and adjuvant therapies. The most common pattern of failure was distant metastasis calling for further optimization of systemic therapy.